Explicit asymptotics for certain single and double exponential sums. Issue 2 (April 2020) - Kalimeris, K.; Fokas, A. S.
Abstract: By combining classical techniques together with two novel asymptotic identities derived in recent work by Lenells and one of the authors, we analyse certain single sums of Riemann-zeta type. In addition, we analyse Euler-Zagier double exponential sums for particular values of Re { u } and Re { v } and for a variety of sets of summation, as well as particular cases of Mordell-Tornheim double sums.